2013
DOI: 10.2355/isijinternational.53.520
|View full text |Cite
|
Sign up to set email alerts
|

Residual Stress Analysis in PVD Coated Austempered Ductile Iron

Abstract: The aim of this work is to study residual stresses (RS) in PVD TiN and CrN coated ADI substrates with different nodule counts, austempering temperatures and surface finishing methods (grinding and polishing). Coatings were applied by arc ion plating using an industrial reactor and different sets of processing parameters. Residual stress measurements were performed by x-ray diffraction using the sin 2 ψ method along two principal axes on the samples surface (parallel and perpendicular to the substrate abrasion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…The surface residual stresses of the coated samples are also compressive, with average values of 3.65 and 5.20 GPa for the Ti/TiN and TiAl/TiAlN samples, respectively. According to a previous work [22], the residual stresses of the coated samples are independent of the measurement direction indicating a rotationally symmetric stress state. An increase in the stress level by the addition of a third element in a binary coating has been previously reported by other authors [25][26][27][28].…”
Section: Accepted Manuscriptmentioning
confidence: 62%
See 1 more Smart Citation
“…The surface residual stresses of the coated samples are also compressive, with average values of 3.65 and 5.20 GPa for the Ti/TiN and TiAl/TiAlN samples, respectively. According to a previous work [22], the residual stresses of the coated samples are independent of the measurement direction indicating a rotationally symmetric stress state. An increase in the stress level by the addition of a third element in a binary coating has been previously reported by other authors [25][26][27][28].…”
Section: Accepted Manuscriptmentioning
confidence: 62%
“…The patterns of the bilayer TiAl/TiAlN coatings, Fig.2 (b [22], ADI residual stresses vary according to the measurement direction, being smaller perpendicular to the grinding marks. The Ra values of the coated samples are close to each other and are higher than the value of uncoated ADI due to the presence of macroparticles (protrusions) in the coatings [23,24].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Moreover, the authors of the present work found a combination of industrial-use processing parameters producing PVD TiN and CrN coatings of acceptable characteristics as far as coating thickness, hardness, residual stresses and adhesion are concerned, causing no significant deterioration of ADI microstructure. Additionally, the analysis of the effects of the substrate characteristics on coating properties evidenced little influence of the austempering temperature and nodule count [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…The experimental results demonstrate that nanohardness is seriously affected by the residual stress [5]. Residual stresses depend on properties of substrates, surface finishing methods and processing parameters [6,7] It was shown that the residual stresses in the coatings deposited with ion assistance depend on the thickness of the coating and the flux and energy of the bombarding ions [8]. It was marked in [9] that residual stresses can arise from three sources: thermal, intrinsic and lattice mismatch.…”
Section: Introductionmentioning
confidence: 99%